Is the Measles Virus Indeed Involved in Carcinogenesis? – Commentary - Benharroch Daniel (International Journal of Negative Results, 2018)
Objectives: An association between the measles virus and Hodgkin lymphoma has been disclosed by our laboratory in Beer-Sheva, starting in 2003. We question the refutation of our study and the absence of interest among experts. Methodology: It was based on immunohistochemistry with commercial, as well as experimental anti-measles antibodies. It relied also on RT-PCR and in situ hybridization evidence of measles virus RNA. Key Results: At this stage (2004), the link between the virus and the lymphoma was essentially descriptive. The first and last response to our challenge appeared in 2007, in the form of doublet articles, in the same issue of a major cancer journal. The two European research groups responding, rejected categorically our findings by proposing different arguments. Major Conclusion: As reservations to these reactions became soon apparent, a series of papers from our laboratory were published. These articles concerned the evidence of a relationship between the measles virus and additional categories of cancers. Different malignancies in which this virus was not expressed at all, were also described. A further study suggested a mechanism by which the measles virus may activate lymphomagenesis in classic Hodgkin lymphoma. To our dismay, and in spite of repeated calls to verify the various results, no further response was obtained from international experts.
Keywords: measles virus